Moyamoya disease manifesting with bilateral involvement of the proximal vertebral arteries: A case report - Omar Alwakaa; Felipe Ramirez-Velandia; Jean Filo; Michael Young; Christopher S. Ogilvy; Justin H. Granstein (Brain Circulation)
Moyamoya disease (MMD) is a cerebrovascular disorder characterized by progressive occlusion of intracranial arteries, often leading to stroke and intracerebral hemorrhage. While MMD classically affects the intracranial vasculature, we present an unusual case of bilateral vertebral steno-occlusion, resulting in vertebrobasilar insufficiency in a 37-year-old man with MMD and treated with angioplasty and stenting of the dominant vertebral artery. Review of the literature demonstrates proximal vertebral artery involvement to be a rare manifestation of moyamoya disease. This report contributes to the understanding of the clinical spectrum of MMD and emphasizes the need for vigilance and awareness of the possibility of extracranial vascular complications in affected individuals.